2014
DOI: 10.4236/ajps.2014.513224
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall Distribution Functions for Irrigation Scheduling: Calculation Procedures Following Site of Olive (<i>Olea europaea</i> L.) Cultivation and Growing Periods

Abstract: In Tunisia (36.5˚N, 10.2˚E, Alt. 10 m), rainfall is the major factor governing olive production. It is characterized by large variability in time and space, making yields of olive trees highly dependent on the amount of water received and timing. Thus, improvement of olive productivity by irrigation is necessary. This study aimed to determine the crop water needs of olive orchards and the rainfall frequencies at which they are covered following age and sites of olive production. For this purpose, the rainfall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…To calculate ET0, there are a lot of empirical formulas using different climatic parameters (Masmoudi-Charfi and Habaieb, 2014;Bchir, 2015). The use of the different empirical formulas depend on available weather data.…”
Section: Evapotranspiration Calculation Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…To calculate ET0, there are a lot of empirical formulas using different climatic parameters (Masmoudi-Charfi and Habaieb, 2014;Bchir, 2015). The use of the different empirical formulas depend on available weather data.…”
Section: Evapotranspiration Calculation Methodsmentioning
confidence: 99%
“…The Blaney-Criddle (BC) equation also gives similar ET0 values (with a lowestimation) to those recorded by the Penman-Monteith (PM) equation. In the case of lack of climate data, Masmoudi-Charfi and Habaieb (2014) found that the Blaney-Criddle formula is positively correlated with the Penman-Monteith equation in different bioclimatic stages of Tunisia. However, the same authors concluded that, at the phenological scale of the olive tree, this formula is effective only during the vegetative rest, the vegetation development, the beginning of the flowering, the fruit growth, the oil synthesis and ripening of olives.…”
Section: Correlations Between the Different Calculating Formulasmentioning
confidence: 97%
See 2 more Smart Citations
“…36.45°E, E: 0 m) in collaboration with the Technical Centre of Citrus (CTA), which is a governmental centre specialized in the promotion and development of the citrus industry. The region is characterized by a typical Mediterranean climate with five to six rainless months, an average annual precipitation of 460 mm, falling mostly from November to March and a Thornwhite aridity index of 0.29 [6]. The experimented citrus orchard was planted in 1998 at 4x5 m 2 spacing.…”
Section: A Study Areamentioning
confidence: 99%